Determinants of the Quality of Government Agency Performance Accountability Reports (Case Study at the Directorate General of Islamic Education the Ministry of Religious Affairs of the Republic of Indonesia) - Maharagita Audimy Tammalea; Nurul Hidayah (Budapest International Research and Critics University, 2022)
This study aims to examine the determinants of the quality of government agency performance accountability report (LAKIP), namely the understanding government accounting standards, quality of human resources, and work motivation. Using a quantitative approach, self-administered questionnaires were used to gather responses from 150 employees of the Republic of Indonesia's Ministry of Religious Affairs, Directorate General of Islamic Education. Analyses were then performed on the obtained data using Partial Least Squares (PLS) method. According to this study's findings, (1) Understanding Government Accounting Standards has a positive and significant effects on the Quality of Government Agency Performance Accountability Report (LAKIP), (2) Quality of Human Resources has a positive and significant effects on the Quality of Government Agency Performance Accountability Report (LAKIP), and (3) Work Motivation has a positive and significant effects on the Quality of Government Agency Performance Accountability Report (LAKIP).